ILLOCUTIONARY ACT IN GUARDIAN OF THE GALAXY MOVIE (2014) - Fahrul Rozi; M. Bahri Arifin; Nasrullah Nasrullah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2021)
The aims of this research are to identify the illocutionary act that performed by Peter Quill and his team that are Gamora, Drax, and Rocket, and also to analyze the context of situation of those illocutionary acts. This research used speech act theory which is the illocutionary act. This research used qualitative research as the design and used content analysis. The data of this research were dialogue, conversation, and statement from the guardian of the galaxy movie. This research has two data sources which is the guardian of the galaxy movie (2014), and the script of film itself. The data of this research have been analyzed uses the illocutionary act. The result of this research found that there are the illocutionary act that has been performed by Peter and his team namely; declarative, assertive, expressive, directives, and commissive. Also from those illocutionary acts which identified by the researcher, it performed with the context of a situation which are setting (s), participant (p), ends (e), act sequence (a), key (k), instrumentalities (i), norms (n), genre (g).